Preferensi Masyarakat Kota Bogor Terhadap Atribut- Atribut Perbankan Syariah Sebagai Landasan Empiris Strategi Pengembangan Perbankan Syariah Di Indonesia - Setiawan, Budi; ., Suharmiati (LPPM Institut Bisnis dan Informatika Kesatuan, 2016)
The purpose of this study is to acknowledge the perceptions on sharia banking attributes in Bogor, to analyse the leading attributes used as preference in Bogor when choosing a sharia bank, and to set the conceptual strategy as an effort to develop the existence of sharia banking in Indonesia. Research population are every citizen of Bogor with the status of head of family. Sample is set with convenience technique measuring 100 heads of family as respondents. Data collection uses questionnaire instruments. Data analysis technique used in this study is using Friedman’s non parametric statistics and Importance Performance Analysis matrix. The results show that the people’s perceptions on sharia banking attributes are categorized into important and fairly important. The attributes considered important are as follow: in accordance with the sharia law, ATM, call centre, comfortable and clean office space, strategic locations, hospitality and fast serving time, secured transaction guarantee, and company’s social responsibility. On the other hand, the attributes considered fairly important are: profit sharing portion, clear procedure, competitive costs, staff’s competencies, and prestige. The leading attributes are non-interest profit sharing, ATM, call centre, image, Islamic ambiance, clean and comfortable office, location, product varieties, procedures, transaction costs, hospitality and fast serving time, secured transaction guarantee, and company’s social responsibility. Conceptual strategies in order to develop sharia banking in Indonesia are categorized as leading priority strategies, performance maintenance, low priority, and elaboration.